A prospective validation of the Bova score in normotensive patients with acute pulmonary embolism. Issue 165 (May 2018) - Bova, Carlo; Vanni, Simone; Prandoni, Paolo; Morello, Fulvio; Dentali, Francesco; Bernardi, Enrico; Mumoli, Nicola; Bucherini, Eugenio; Barbar, Sofia; Picariello, Claudio; Enea, Iolanda; Pesavento, Raffaele; et al.
Abstract: Background: The Bova score has shown usefulness in the identification of intermediate-high risk patients with acute pulmonary embolism (PE), but lacks prospective validation. The aim of this study was to prospectively validate the Bova score in different settings from the original derivation cohort. Methods: Consecutive, normotensive patients with acute PE recruited at 13 academic or general hospitals were stratified, using their baseline data, into the three Bova risk stages (I–III). The primary outcome was the 30-day composite of PE-related mortality, hemodynamic collapse and non-fatal PE recurrences in the three risk categories. Results: In the study period, 639 patients were enrolled. The primary end point occurred in 45 patients (7.0%; 95% Confidence Intervals, 5.2%–9.3%). Risk stage correlated with the PE-related complication rate (stage I, 2.9%; stage II, 17%; stage III, 27%). Patients classified as stage III by the Bova score had a 6.5-fold increased risk for adverse outcomes (3.1–13.5, p < 0.001) compared with stages I and II combined. Rescue thrombolysis increased from stage I to stage III (0.6%, 12% and 15% respectively). All-cause mortality (5.3%) did not substantially differ among the stages. Conclusions: The Bova score accurately stratifies normotensive patients with acute PE into stages of increasing risk of 30-day PE-related complications. Highlights: The Bova score has received so far only retrospective validations. In this prospective study adverse events due to pulmonary embolism were linked with the Bova stages. Patients at Bova stage III had a 6.5-fold increased risk for adverse outcomes compared with stages I and II combined.